Hellbenders [videorecording (DVD)] - Petty, J. T. (John T.); Collins, Clifton, Jr; Brown, Clancy; Rikoon, Robyn
Hellbenders follows the exploits of the Brooklyn-based Augustine Interfaith Order of Hellbound Saints, known as Hellbenders, a team of lewd and blasphemous ministers who live in a constant state of debauchery in order to be damnation-ready so they can drag the worst of demons back to Hell. When one of the foulest demons possesses one of their own and threatens the existence of both Brooklyn and the world, the Hellbenders' faith is tested.